2015
DOI: 10.1002/ajmg.a.37159
|View full text |Cite
|
Sign up to set email alerts
|

Report of a case of Raine syndrome and literature review

Abstract: We report on a case of Raine syndrome with a mutation in FAM20C and typical phenotypic features consisting of midface hypoplasia, hypoplastic nose, choanal atresia, wide fontanelle, exophthalmos, generalized osteosclerosis and intracranial calcification. New features in our patient are cerebellar hypoplasia and pachygyria. We review the literature and conclude that the triad of hypoplastic nose, exophthalmos and generalized osteosclerosis and/or intracranial calcification is consistent in all molecularly confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
(34 reference statements)
3
22
0
Order By: Relevance
“…To date, 28 pathogenic variants in FAM20C have been reported in association with Raine syndrome of which 19/28 are missense variants (Acevedo et al, ; Boissel et al, ; Elalaoui et al, ; Fradin et al, ; Kochar et al, ; Mahmood N., 2014; Rafaelsen et al, ; Seidahmed et al, ; Sheth et al, ; Simpson et al, ; Simpson et al, ; Takeyari et al, ; Tamai et al, ; Whyte et al, ) (Table S1). These 19 reported pathogenic missense variants and polymorphisms identified in nominally healthy reference population were mapped onto the 3D structure of the FAM20C protein (Berman et al, ; Lek et al, ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 28 pathogenic variants in FAM20C have been reported in association with Raine syndrome of which 19/28 are missense variants (Acevedo et al, ; Boissel et al, ; Elalaoui et al, ; Fradin et al, ; Kochar et al, ; Mahmood N., 2014; Rafaelsen et al, ; Seidahmed et al, ; Sheth et al, ; Simpson et al, ; Simpson et al, ; Takeyari et al, ; Tamai et al, ; Whyte et al, ) (Table S1). These 19 reported pathogenic missense variants and polymorphisms identified in nominally healthy reference population were mapped onto the 3D structure of the FAM20C protein (Berman et al, ; Lek et al, ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐six additional individuals with Raine syndrome have been reported to date, delineating its phenotypic spectrum which includes a consistent and well‐defined facial gestalt‐midface hypoplasia, proptosis, micrognathia, high and/or cleft palate, hypoplastic nose with depressed nasal bridge, low‐set ears, generalized osteosclerosis, fracture‐like rib lesions, and intracerebral calcifications. Affected individuals are typically short and have micro‐ and/or brachycephaly with wide open anterior and posterior fontanelles (Faundes et al, ; Seidahmed et al, ; Sheth, Bhavsar, Gandhi, Sheth, & Pancholi, ). Most newborns with the severe form die of respiratory failure due to pulmonary hypoplasia and small thorax within a few hours to weeks of life, although individuals with the milder form have been reported to live into adulthood, confirming the presence of a continuous phenotypic spectrum (Faundes et al, ; Seidahmed et al, ; Sheth et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF23 levels could be studied in a few cases and shown to be elevated [4,5,28,39], but elevated urinary phosphate excretion had been shown in almost all cases including the case herein [24,27,28,34,39]. However, serum phosphate levels were found to be normal in some of the patients [4,20,[32][33][34][35]. Additionally, the development of hypophosphatemia in cases with normal phosphate levels is also detected in later ages, in puberty and in adulthood [34].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that FAM20C catalyzes the attachment of phosphates to serine residues in the Ser-X-Glu (S-X-E) motifs of secretory proteins, which include dentin matrix protein 1 (DMP1) and osteopontin (OPN), two members of the “Small-Integrin-Binding LIgand, N-linked Glycoproteins” (SIBLING) family 26 . Inactivating mutations in the human FAM20C gene cause Raine syndrome, an autosomal recessive disorder that demonstrates a variety of manifestations 711 . Some Raine syndrome patients die shortly after birth 7, 12 , while others may live into middle childhood or even middle adulthood 810 .…”
Section: Introductionmentioning
confidence: 99%